How can sport promote adolescent mental health? A qualitative study from the rural plains of Nepal - Joanna Morrison; Damodar Rimal; Indira Pradhan; Nagendra P. Luitel; Kelly Rose-Clarke (SSM - Mental Health, 2025)
Sport holds potential to deliver adolescent mental health promotion, which is particularly important in low resource settings where there is high burden but lack of access to specialist services. We conducted a qualitative study in rural plains Nepal to describe adolescent stressors and coping strategies and analyse the mechanisms through which sport may promote or undermine mental health. We collected data from 81 adolescents, caregivers, teachers, coaches, and health workers through interviews, group discussions, and group walks. We used an interpretive descriptive approach to data collection and analysis. We found that adolescents were anxious about financial pressures on households, romantic relationships and relationships within families. Academic pressure and harassment of girls was common. Poor achievement in sport and resultant ridicule and loss of social status was also a source of shame and stress. Conversely, if adolescents participated in sport within a supportive environment, it provided opportunities for increased self-esteem, strong social support networks, development of discipline and stress release. We suggest five main areas of importance to consider when designing and implementing sport for mental health promotion interventions: 1)Involving communities, adolescents and caregivers in design, implementation and evaluation to prevent tensions and create a joint vision for how sport can support adolescents 2)Engaging with the social determinants of health 3) Developing adolescent coping strategies and signposting mental health support 4)Addressing fear of failure and lack of body confidence through creating a supportive, inclusive environment 5)Addressing negative gendered social norms. We show how sport interventions can be developed to support adolescent mental health through acknowledging and responding to complex community contexts.